No Choice but Welcoming Refugees - Heriyanto, Dodik Setiawan Nur; Sefriani, Sefriani; Tamas, Fezer (Lentera Hukum, 2023)
The non-refoulement principle requires each country to consider refugees and asylum seekers in their country of origin if they are subject to persecution and threaten their lives. As a geographically strategic country, Indonesia has been a significant crossroad for international refugees and asylum seekers often consider Indonesia their temporary destination. Moreover, the complex situation of international refugees has encouraged to reinterpret of the principle of non-refoulement into various national measures and domestic policies, given that Indonesia is deemed a transit country for refugees and has not ratified the 1951 Convention on the Status of Refugees. This paper aims to analyse the concept of refugee protection under international law, particularly the non-refoulement principle and investigate the application of the non-refoulement principle in Indonesia. This study employed normative and empirical legal research with statutory, conceptual, and comparative approaches. This study confirms that the non-refoulement principle is part of jus cogens norms in international law but does not fit in its application. Indonesia has inconsistency in upholding the non-refoulement principle into the binding normative rules. Refugees have received far less attention from the Indonesian government due to insufficient infrastructure and financial allocation. Moreover, the existing executive regulations do not provide effective enforcement since these regulations have a lower position in the hierarchy and cannot have deterrent sanctions. Hence, ratification of the 1951 Convention is urgently needed by Indonesia to guarantee the protection of refugees within its jurisdiction. At the regional scope, Indonesia can encourage ASEAN countries to adopt good practices in the European Union to set sharing quotas to ensure that not most refugees escape to Indonesia.Keywords: Customary International Law, Indonesia, Refugees.